CRIM-negative infantile Pompe disease: Characterization of immune responses in patients treated with ERT monotherapy - Berrier, Kathryn L. (Genet Med, 2015)
PURPOSE: Enzyme replacement therapy (ERT) with recombinant human GAA (rhGAA) prolongs survival in infantile Pompe disease (IPD). However, the majority of cross reactive immunologic material (CRIM)-negative (CN) patients have immune responses with significant clinical decline despite continued ERT. We aimed to characterize immune responses in CN IPD patients receiving ERT monotherapy. METHODS: A chart review identified 20 CN IPD patients treated with ERT monotherapy for ≥6 months. Patients were stratified by anti-rhGAA antibody titers: high sustained antibody titers (HSAT) ≥51,200 at least twice; low titers (LT) <6,400 throughout treatment; or sustained intermediate titers (SIT) 6,400–25,600. RESULTS: Despite early initiation of treatment, the majority (85%) of CN patients developed significant antibody titers, most with HSAT associated with invasive ventilation and death. Nearly all patients with HSAT had at least one nonsense GAA mutation, while the LT group exclusively carried splice site or frameshift mutations. Only one patient in the HSAT group is currently alive after successful immune modulation in the entrenched setting. CONCLUSION: Immunological responses are a significant risk in CN IPD; thus, immune tolerance induction in the naïve setting should strongly be considered. Further exploration of factors influencing immune responses is required, particularly with the advent of newborn screening for Pompe disease.